2017
DOI: 10.1007/s11255-017-1685-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of abdominal artery calcification in dialysis patients with end-stage renal disease: a systematic review and meta-analysis

Abstract: The pooled and nearest estimate of AAC prevalence among dialysis patients was as high as 65%. Geographical region, AAC detection instruments, age of participants, and male proportion potentially lead to the high variance of the reported prevalence. Considering the high AAC prevalence, effective treatment for preventing vascular calcification in these patients is badly needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 68 publications
4
16
0
Order By: Relevance
“…Abdominal artery calcification is particularly common in dialysis patients, with the overall prevalence ranging from one third to more than 80 percent [4,[14][15][16]. We reported an abdominal artery calcification prevalence of 57.2% in our PD patients, in correspondence with published meta results in Asia population [4].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Abdominal artery calcification is particularly common in dialysis patients, with the overall prevalence ranging from one third to more than 80 percent [4,[14][15][16]. We reported an abdominal artery calcification prevalence of 57.2% in our PD patients, in correspondence with published meta results in Asia population [4].…”
Section: Discussionsupporting
confidence: 86%
“…Abdominal artery calcification is particularly common in dialysis patients, with the overall prevalence ranging from one third to more than 80 percent [4,[14][15][16]. We reported an abdominal artery calcification prevalence of 57.2% in our PD patients, in correspondence with published meta results in Asia population [4]. There were a few cross-sectional studies suggesting that abdominal artery calcification might be less common in PD patients compared to HD patients [14], while other studies reported no advantage of one modality over the other [4,17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abdominal artery calcification is particularly common in dialysis patients, with the overall prevalence ranging from one third to more than 80% [4,[14][15][16]. We reported an abdominal artery calcification prevalence of 57.2% in our PD patients, in correspondence with published meta results in Asia population [4].…”
Section: Discussionsupporting
confidence: 87%
“…Arterial calcification is associated with great risks of cardiovascular disease (CVD) among patients with different chronic kidney disease (CKD) stages, which translates into excess cardiovascular mortality in this population [1,2]. It has been well established that vascular calcification is more prevalent in CKD patients, especially those on dialysis, than that in the age-matched general population [3,4]. Several imaging techniques have been utilized in the evaluation of vascular calcification, such as ultrasonography, computed tomography (CT), mammograms and plain radiographs [5][6][7].…”
Section: Introductionmentioning
confidence: 99%